A NEW FIELD TEST WITH DIFFERENT FLOORS TO MEASURE DYNAMIC BALANCE AMONG PRESCHOOL CHILDREN - Topcu, Zehra Guchan; Hacikucuk, Hatice; Cetintas, Erdogan; Tomac, Hayriye; Obuz, Tugba; Seker, Nazan; Eker, Levent (Dokuz Eylul Univ Inst Health Sciences, 2024)
Purpose: This study aimed to assess the test -retest reliability and inter -rater reliability of a newly designed balance test named the Paediatric Tandem Balance (PTB) test. Material and Methods: 108 children (girls: 54, boys: 54) with a mean age of 4.08 +/- 0.78 were included in the study. Two raters measured the same children for inter -rater reliability, and the first rater retested the same children after two days for test -retest reliability. Time and sway numbers were recorded as the variables of the PTB test. Results: The inter -rater reliability was good in both parameters of PTB which were duration (r=0.836) and number of sways (r=0.840). The test -retest reliability was good in both duration (r=0.727) and number of sways (r=0.705). The PTB test is a reliable test to measure dynamic balance in 3-5 years old children. Conclusion: This test will bring a new point of view for tests of dynamic balance.
Keywords: balance; balance test; dynamic balance; postural control